Materiality and discourse: toward a relational understanding of marginalizing onto-epistemologies in the ivory tower - Varela, Elisa M., author; Griffin, Cindy L., advisor; Williams, Elizabeth A., committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2016)
Using epistemological and ontological lenses, this communicative study interrogates the experiences of the graduate community within the communication studies discipline. Specifically, and building on feminist methodologies and intersectional approaches, I seek to identify experiences of graduate students of color that call out and illuminate everyday discourses of silencing, erasure of difference, and disciplining. Additionally, I hope to identify not only these discourses, but also the ways in which corporeality and materiality become alongside these. One goal of this work is to encourage increased critical discussion around discursive theoretical and methodological approaches to scholarship within and beyond communication studies. A second, broader goal is to problematize and expand understanding(s) regarding how fragmented Western epistemological and ontological conceptual frameworks might actually "emulsify" and "curdle" to constitute complex somatic-semiotic matrices of domination (Hill-Collins, 2000) and emancipation within the academy.
Keywords: materiality and discourse; ontology; relationality; methodology; epistemology; race